ANALISIS FRAMING PEMBERITAAN TRIBUN-TIMUR.COM TENTANG DEMONSTRASI MAHASISWA UNIVERSITAS MUHAMMADIYAH MAKASSAR - Dian Muhtadiah; Natasyah Dewanty (Departement of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2023)
Demonstrations displayed by the mass media are always associated with violence and crime, creating conflict scenarios involving demonstrators and the police. The Makassar East Tribune media also reporterd on demonstrations that were often carried out by students. This study aims to analyze how the online portal Tribun Timur.com frames news about demonstrations carried out by students of Muhammadiyah Makassar University. This study uses a qualitative descriptive approach using Zhongdang Pan and Gerald M. Kosicki’s framing analysis method, with 4 structure namely syintax, script, thematic and rethorical. Data collection techniques through observation, interviews, and documentation. Based on the results of the research by analyzing 5 news stories, the researcher saw that the news presented by Tribun Timur.com had fulfilled the four structures, namely syntax, script, thematic and rethorical. The tribune focused more on the road blockade by students. News of the demonstration can harm the institution, namely the University of Muhammadiyah Makassar, but students do the opposite. The news narrative displayed by Tribun Timur.com can be said to be short. This is because the Tribune presents breaking news, where news is presented briefly and quickly, followed by follow up news.